The future low-carbon value chain framework in selected Philippine industries using scenario building - De Villa, Yoshiko Zoe; Imbang, Prof. Glen A. (Quezon City University of the Philippines Diliman, 2017)
This project paper is concerned on the assessment of the future supply chain model of the automotive, healthcare, and food production industries as the global economy, including the Philippines, transitions to a low-carbon. Furthermore, a quick assessment on the sources of emissions and how the value chain activities can adopt to the transition has been conducted. The scenario building process was the tool used in this project paper.

The scenario building process aimed at providing futuristic view of the issue of concern in consideration of the key driving forces. This project paper concluded that the legal framework is the key driving force to a low-carbon economy. Specifically, the legal framework pertained to the Paris Agreement, Philippine Climate Change Act of 2009 or Republic Act 9729, and Executive Order 174 or the Institutionalization of the Philippine-GHG Inventory Management and Reporting System. Conversely, economic and social factors such as finance mechanisms, monopoly by large multinational corporations, carbon taxation, and green procurement were the pivot variables of food production, automotive, and healthcare industries, respectively. These have high impact in the value chain activities of the selected industries but the uncertainty was still very high. One thing is highly certain by 2020; that GHG inventory and reporting will be a crucial part across businesses. Through this, it was concluded that the GHG inventory and reporting system will be an important tool in the transition to a low-carbon economy as it will make businesses across the selected industries realize their emissions, and in effect their reduction potential. The full transition to a low-carbon economy is plausible but will not be realized by 2020.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Business logistics; Scenario building; Supply chain models